Biometrics of Psoas Minor Muscle in North Indian Population - Sachin P.; Suchismita G.; Neelam V. (Department of Surgery, UKM Medical Centre, 2015)
Psoas minor is classified as an inconstant muscle which is frequently absent. It is a muscle of posterior abdominal wall, lying anterior to the psoas major. The psoas minor is a weak flexor of the lumbar vertebral column and is innervated by the anterior ramus of nerve L1. Previous literatures lack proper description about the morphology and function of this muscle. Psoas minor muscle has been associated with a painful condition of abdomen, the psoas minor syndrome. We conducted a study on 20 formalin fixed cadavers in relation to prevalence, morphology, variations and morphometry of psoas minor muscle. It was found, that the percentage of absence of psoas minor muscle was 65%. No anatomical variation of the muscle was seen. Morphometric analysis demonstrated the average total length of muscle to be 215.2 mm, average length of muscle belly 67.7 mm, average tendon length 145.7 mm, while average width and thickness of muscle were 13.6 mm and 3.4 mm, respectively. This study provides valuable information on psoas minor muscle which may help in proper understanding of anatomy, function and clinical importance of the muscle.